2019
DOI: 10.1111/csp2.86
|View full text |Cite
|
Sign up to set email alerts
|

Early detection and spatial monitoring of an emerging biological invasion by population genetics and environmental DNA metabarcoding

Abstract: Rapid management responses against invasive species soon after their establishment are the most efficient way to limit their biological and economic impacts. Early detection and reliable monitoring is however challenging when cryptic taxa are involved. Here we show how environmental DNA (eDNA) metabarcoding of water samples efficiently unveiled an emerging invasion of Italian crested newts (Triturus carnifex), one of the most successful amphibian invaders in Europe. We compared and validated an eDNA survey by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…In a subset of eleven T. carnifex/hybrids from the study area, we consistently observed the ND4-haplotype CIII10/11. This haplotype has previously been reported from central Italy (Mulino di Pianoro, Emilia-Romagna; Minucciano, Tuscany; Canestrelli et al, 2012) and the non-native T. carnifex population near Basel (Dufresnes et al, 2019).…”
Section: Mitochondrial Genetic Statussupporting
confidence: 70%
See 2 more Smart Citations
“…In a subset of eleven T. carnifex/hybrids from the study area, we consistently observed the ND4-haplotype CIII10/11. This haplotype has previously been reported from central Italy (Mulino di Pianoro, Emilia-Romagna; Minucciano, Tuscany; Canestrelli et al, 2012) and the non-native T. carnifex population near Basel (Dufresnes et al, 2019).…”
Section: Mitochondrial Genetic Statussupporting
confidence: 70%
“…Apart from their natural hybrid zone, the two species co‐occur along artificial contact zones caused by human translocations of T. carnifex into the native range of T. cristatus . Such introductions have been reported from several European countries (UK: Brede, 2000; Brede, 2015; Griffiths, 1996, Switzerland: Arntzen & Thorpe, 1999; Dufresnes et al, 2016; Dufresnes et al, 2019, the Netherlands: Bogaerts, 2002; Meilink et al, 2015; Wielstra et al, 2016, and Germany: Franzen et al, 2002; Maletzky et al, 2008). These introductions deserve special attention by conservationists, because both species face a strong decline throughout their native ranges, and introgressive hybridization between the two species may potentially lead to “genetic pollution” (Butler, 1994).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Those two protocols differ mainly in the eDNA collection step, each protocol using a distinct filter, with different membrane composition, surface, and pore size, leading also to different volumes of filtered water and in the extraction step, with two different extraction kits and different sample preparation prior to the extraction (Figure 1a). Those two protocols were used in many rivers and streams throughout the world including Europe, South America, and Asia (Cantera et al, 2019;Cilleros et al, 2019;Civade et al, 2016;Dufresnes et al, 2019;Lopes et al, 2017;Milhau et al, 2019;Pont et al, 2019;Sasso et al, 2017;Spitzen -van der Sluijs et al, 2020;Vimercati et al, 2020). It is F I G U R E 1 eDNA workflow for the two considered protocols (a) and sampling site locations (b) therefore important to test the robustness of eDNA results to such variations in protocols to determine whether the data acquired using distinct protocols deserve to be merged and ultimately if they can, or not, be used jointly for biodiversity and conservation studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is in marked contrast to how conservation genetics currently works. Most applied studies in conservation genetics are carried out by researchers or in close collaboration with academic institutions, zoological and botanical gardens or museums (Dufresnes et al 2019). This fact prompts the question whether one needs to make conservation genetics a routine method-similar to the above examples-that can be readily applied by governmental authorities, NGOs, environmental consultancies and private-sector companies?…”
Section: Introductionmentioning
confidence: 99%